2017
DOI: 10.1016/j.watres.2017.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Porosity of spacer-filled channels in spiral-wound membrane systems: Quantification methods and impact on hydraulic characterization

Abstract: The porosity of spacer-filled feed channels influences the hydrodynamics of spiral-wound membrane systems and impacts the overall performance of the system. Therefore, an exact measurement and a detailed understanding of the impact of the feed channel porosity is required to understand and improve the hydrodynamics of spiral-wound membrane systems applied for desalination and wastewater reuse. The objectives of this study were to assess the accuracy of porosity measurement techniques for feed spacers differing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…The channel porosity can be calculated using Equation (2). In the present work, a different element length meant a different porosity of the feed channel, and the value was higher than in other feed spacer studies, where the maximum value of the porosity measurement was 0.906 as reported by Siddiqui et al [42]. In this study, the porosity value of the elliptic cross-section was from 0.928 to 0.979, as shown in Figure 4.…”
Section: Porositysupporting
confidence: 45%
“…The channel porosity can be calculated using Equation (2). In the present work, a different element length meant a different porosity of the feed channel, and the value was higher than in other feed spacer studies, where the maximum value of the porosity measurement was 0.906 as reported by Siddiqui et al [42]. In this study, the porosity value of the elliptic cross-section was from 0.928 to 0.979, as shown in Figure 4.…”
Section: Porositysupporting
confidence: 45%
“…It can be concluded that the porosity of spacer-filled channels does not only influence the hydrodynamics of spiral-wound membrane systems but impacts the overall performance of the system [30]. It can be concluded that the porosity of spacer-filled channels does not only influence the hydrodynamics of spiral-wound membrane systems but impacts the overall performance of the system [30].…”
Section: Permeate Spacer Characteristicsmentioning
confidence: 99%
“…The latter influences the porosity of the material that is a crucial parameter for any hydrodynamic predictions [30]. Permeate spacers particularly differ in height and mesh size.…”
Section: Permeate Spacer Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations